A Literature Review of Research in Bug Resolution: Tasks, Challenges and Future Directions - Zhang, Tao; Jiang, He; Luo, Xiapu; Chan, Alvin T.S. (Computer journal, 2016)
Due to the increasing scale and complexity of software products, software maintenance especially on bug resolution has become a challenging task. Generally in large-scale software programs, developers depend on software artifacts (e.g., bug report, source code and change history) in bug repositories to complete the bug resolution task. However, a mountain of submitted bug reports every day increase the developers' workload. Therefore, 'How to effectively resolve software defects by utilizing software artifacts?' becomes a research hotspot in software maintenance. Considerable studies have been done on bug resolution by using multi-techniques, which cover data mining, machine learning and natural language processing. In this paper, we present a literature survey on tasks, challenges and future directions of bug resolution in software maintenance process. Our investigation concerns the most important phases in bug resolution, including bug understanding, bug triage and bug fixing. Moreover, we present the advantages and disadvantages of each study. Finally, based on the investigation and comparison results, we propose the future research directions of bug resolution.